UPAYA KOMUNITAS SAMIN DI KUDUS JAWA TENGAH DALAM MEMPERTAHANKAN JATI DIRI DI TENGAH PROBLEMATIKA KEHIDUPANNYA - Rosyid, Moh (Masyarakat Indonesia, 2018)
Samin community has existed since the Dutch colonial era. This community was lead by Ki Samin Surosentiko to fight against the Dutch which was started in Blora and then spreaded to surrounding regions in Central Java, such as Pati, Grobogan, and Kudus. Now, Samin community in Kudus keeps following their ancestor’s teachings, such as cling to their belief (Adam), refuse to register their marriage, not going to formal education since Ki Samin considered joining formal education is as the same as obeying the Dutch colonial, and also prefer to wear their traditional outfit. Nowadays, they faces several problems as their belief to not register their marriage, lacking of formal education, a failed farming lead to urbanization, and the absent of prominent figure among Samin community caused by various interpretations of oral teachings. This study uses descriptive analysis and based on data research conducted in 2016 through interviews, observations, and forum group discussion.